THE INFLUENCE OF INFLUENCER CREDIBILITY ON CONSUMER PURCHASE INTEREST WITH PRICE AS A MODERATING VARIABLE - Ni Ketut Karwini; Ni Kadek Suryani (ITB AAS Indonesia Surakarta, 2024)
Abstract Researchers believe that an Influencer has credibility and can make potential consumers decide to buy a product based on the trust that comes from the Influencer's good credibility. Based on this, this research aims to analyze the influence of Influencer Credibility on Purchasing Decisions. Different from a number of other studies, this research adds the price variable as a moderating variable which can strengthen the influence of the Influencer Credibility variable on Purchasing Decisions. This research is quantitative research with an exploratory approach which uses previous research related to Influencer Credibility, Purchasing Decisions, and Price as a benchmark for finding elements of novelty in subsequent research. The data used in this research uses primary data obtained from Suzuki sales spread throughout Indonesia with 300 employees. These data were analyzed using the smart PLS 4.0 analysis tool. The result in this research show that the Influencer Credibility variable can have a positive relationship and have a significant influence on purchasing decisions because the P-Values results are positive and are below the 0.05 significance level, namely 0.017. These results were obtained due to consumer trust in Influencers who have good credibility. Apart from that, in the second row of the third table the Path Coefficient is also the second hypothesis in this research, showing that the Price variable can strengthen the influence of the Influencer Credibility variable on Purchasing Decisions. With affordable prices and service accompanied by good Influencer Credibility, it can make consumers more confident in making purchasing decisions. This statement can be proven from the results of the P-Values which show a positive relationship and a significant influence because it is below 0.05, which is 0.000, more significant than the direct test of 0.012. Based on these results, the first and second hypotheses in this research can be accepted and proven. Keywords: Influencer Credibility, Consumer Purchase, Price